The Impact of Artificial Intelligence on the Legislative Policy of Copyright: Challenges and a Response - Davtyan, T. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The article discusses 56 the main aspects of the interaction of the so-called autonomous artificial intelligence systems and the concepts of Copyright and Related Rights. It reveals leading positions in the professional literature on the following important issues: does the artificial intelligence of the current generation eliminate the monopoly of a human to creativity and it can be said that such an artificial intelligence can “create” unique “works” in the field of science, literature and art. If not, should the results obtained or received by such artificial intelligence systems that are comparable, similar, and sometimes even surpass the original human works, have legal protection in the framework of Copyright or Related Rights? If so, which framework should be available for providing such legal protection, on what grounds, who should be the original right owner of the results obtained by artificial intelligence, what rights should be granted, and what should be the term of such protection
Keywords: artificial intelligence, neural networks, machine learning, intellectual property, copyright, related rights, originality, human authorship, information technology